The Blessings and Curses of Big Time Football: One Perspective - Martin, Michael (Journal of Intercollegiate Sport, 2013)
Drawing from experiences as a leader at various universities, in this paper, the author discusses the blessings and curses of major intercollegiate athletic programs. Blessings include national attention, contribution to diversity, improved facilities, campus excitement, the ability to recruit top coaches and staff, and academic support. Curses include the considerable national attention, tighter scrutiny, misplaced priorities, a culture of dependency, decreases in faculty and staff morale, the potential for decrease athlete welfare, and a lack of competition. The author then offers potential solutions to these issues.